How do you solve using completing the square method #3x^2 + 5x = -x + 4#?

2 Answers
Jun 26, 2018

Answer:

#x = -1 +- sqrt(7/3)#

Explanation:

#3x^2 + 5x = - x + 4#

#3x^2 + 6x = 4#

#(sqrt3 x)^2 + 2 * sqrt3 * sqrt3 x + (sqrt3)^2 = 4 + (sqrt3)^2#

#(sqrt3 x + sqrt3)^2 = 7#

#(sqrt3 x + sqrt3) = +-(sqrt7)#

#x + 1 = sqrt(7/3)#

#x = -1 +- sqrt(7/3)#

Jun 26, 2018

Answer:

#x = -1 +- sqrt(7/3)#

Explanation:

#3x^2 + 5x = -x + 4#

#3x^2 + 6x = 4#

#x^2 + 2x = 4/3#

#x^2 + 2x + 1 = 4/3 = 1 = 7/3#

#(x + 1)^2 = (sqrt(7/3))^2#

#x = 1 = +- sqrt(7/3)#

#x = -1 +- sqrt(7/3)#